2020
DOI: 10.1136/inp.m455
|View full text |Cite
|
Sign up to set email alerts
|

Update on caseous lymphadenitis in sheep

Abstract: Background: Caseous lymphadenitis (CLA), caused by the gram-positive bacteria Corynebacterium pseudotuberculosis, has been present in Great Britain since the 1980s and is now considered endemic. CLA is considered to be an iceberg disease; that is, it is a production-limiting disease, characterised by slow insidious onset, that has production-limiting effects in a larger proportion of the flock than is exhibiting clinical signs at any given point in time.Aim of the article: The disease has been previously revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…These results were supported by Pepin and Paton, who stated that the probability of developing internal lesions of CLA increased with age [8]. However, other studies have described the superficial form as the most prevalent in sheep [43] and also in goats [44]. In Iran, the authors found that 75.70% of the animals were affected by the cutaneous presentation and 24.30% by the visceral form [19].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These results were supported by Pepin and Paton, who stated that the probability of developing internal lesions of CLA increased with age [8]. However, other studies have described the superficial form as the most prevalent in sheep [43] and also in goats [44]. In Iran, the authors found that 75.70% of the animals were affected by the cutaneous presentation and 24.30% by the visceral form [19].…”
Section: Discussionmentioning
confidence: 61%
“…Diagnostic imaging techniques, especially ultrasonography and computed tomography, can be very useful tools to diagnose the visceral form of the disease [39][40][41]. Furthermore, in order to eradicate the disease, ELISA test can be performed, although with a sensitivity of 87% and a specificity of 98% [42], prolonging the testing period, and extending time to eradication can occur, having consequences for the economic value of the flock [43].…”
Section: Discussionmentioning
confidence: 99%
“…Various Corynebacterium phylotypes and have been identified in the sheep vaginal microbiota in previous studies (Swartz et al, 2014;Serrano et al, 2020), as well as in cultivation-based studies (Sawyer, 1977;Manes et al, 2018). Certain members within the Corynebacteriaceae family are known ovine pathogens, such as Corynebacterium pseudotuberculosis, which causes caseous lymphadenitis (Gascoigne et al, 2020). However, it is currently unknown if these OTUs, which showed higher abundance in nonpregnant animals than in pregnant animals, contribute to the negative outcome of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…This review highlights the broad variety of toxic organic/inorganic compounds and plants that may be involved in states of emaciation, wasting, and loss of productivity in sheep. These conditions should be thus considered as differential diagnoses, especially in those animals and flocks where the classic infectious and parasitic wasting diseases have been ruled out [ 1 , 2 , 3 , 4 ]. Diagnosis may be fastidious in many cases, since lesions could be minimal and/or unspecific, and a good anamnesis focused on revealing a history of exposure should be the cornerstone of the diagnostic work-up.…”
Section: Discussionmentioning
confidence: 99%
“…There are several diseases of sheep that may cause wasting, leading to decreased productivity and economic losses in sheep flocks as a result. Johne’s disease, maedi-visna, caseous lymphadenitis, and several parasitic diseases, amongst others, have been traditionally included under the umbrella of the so-called “thin ewe syndrome”, a concept that encompasses several diseases with wasting as the main clinical sign [ 1 , 2 , 3 , 4 ]. Hence, this concept has included mostly infectious and parasitic disorders, probably underestimating the role of other disease causes.…”
Section: Introductionmentioning
confidence: 99%